Evaluation of Applying a Combination of Red Cell Indexes and Formulas to Differentiate β-Thalassemia Trait from Iron Deficiency Anemia in the Thai Population - Pornprasert S. (2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Red cell indexes and formulas have been established as simple, fast, and inexpensive tools to differentiate β-thalassemia (β-thal) trait from iron deficiency anemia. However, none of them showed 100.0% sensitivity and specificity. Moreover, one index may show greater sensitivity and specificity in one population but is ineffective in another population. This study evaluated the diagnostic reliability of a combination of two red cell indexes [red blood cell (RBC) and red blood cell distribution width (RDW)] and nine formulas called ‘11T score’ for differentiation of β-thal trait and iron deficiency anemia in the Thai population. A total of 103 cases, 67 β-thal trait and 36 iron deficiency anemia, Thai subjects with microcytic hypochromic anemia [mean corpuscular volume (MCV) < 80.0 fL and mean corpuscular hemoglobin (Hb) (MCH) < 27.0 pg] were involved in this retrospective study. The results showed that the 11T score with a cutoff value of 7 was able to discriminate between β-thal trait and iron deficiency anemia with sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and efficiency (EFF) higher than 70.0%. It also had 85.4% of correctly identified cases and the highest value of Youden’s Index (YI) (73.8%) when compared to the 11T score with other cutoff values (5, 6, 8 and 9) and other indexes. Thus, the 11T score with the cutoff value of 7 could be used to differentiate β-thal trait from iron deficiency anemia in the Thai population.